2022
DOI: 10.1021/acs.jmedchem.1c01782
|View full text |Cite
|
Sign up to set email alerts
|

Small Amphiphilic Peptides: Activity Against a Broad Range of Drug-Resistant Bacteria and Structural Insight into Membranolytic Properties

Abstract: We report the synthesis and antibacterial activities of a series of amphiphilic membrane-active peptides composed, in part, of various nongenetically coded hydrophobic amino acids. The lead cyclic peptides, 8C and 9C, showed broad-spectrum activity against drug-resistant Gram-positive (minimum inhibitory concentration (MIC) = 1.5−6.2 μg/mL) and Gram-negative (MIC = 12.5−25 μg/ mL) bacteria. The cytotoxicity study showed the predominant lethal action of the peptides against bacteria as compared with mammalian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Antibacterial activity assays indicated that most of Compound 6 exhibited significant antibacterial activities against antibiotic-resistant Gram-positive strains but no obvious effects on Gram-negative strains, which demonstrated that these as-synthesized biphenyl and dibenzofuran derivatives have certain selectivity. The MIC values to MRSA of Compounds 6i and 6m were, respectively, 6.25 and 3,13 μg/mL, which are comparable to values reported in the literature [ 39 , 46 ]. On the other hand, the MIC value to MREF of Compound 6l was 6.25 μg/mL, which indicates greater inhibitory activity than that of 4-methoxy-1-(methylthio)dibenzo[ b,d ]furan-2,3-diol (MIC = 12.5 μg/mL), reported by Gao [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…Antibacterial activity assays indicated that most of Compound 6 exhibited significant antibacterial activities against antibiotic-resistant Gram-positive strains but no obvious effects on Gram-negative strains, which demonstrated that these as-synthesized biphenyl and dibenzofuran derivatives have certain selectivity. The MIC values to MRSA of Compounds 6i and 6m were, respectively, 6.25 and 3,13 μg/mL, which are comparable to values reported in the literature [ 39 , 46 ]. On the other hand, the MIC value to MREF of Compound 6l was 6.25 μg/mL, which indicates greater inhibitory activity than that of 4-methoxy-1-(methylthio)dibenzo[ b,d ]furan-2,3-diol (MIC = 12.5 μg/mL), reported by Gao [ 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…Thus, it seems that as the hydrophobic bulk increases, the ability of the peptide to discriminate between the anionic bacterial surface and the zwitterionic mammalian membrane decreases. These outcomes are in agreement with many previous reports, 96,97 including ours. Furthermore, we calculated the therapeutic index for MRSA cells by dividing HC 50 values with the MICs against MRSA (Table 1).…”
Section: Synergistic Studiesmentioning
confidence: 99%
“…A spherical cutoff function (12 Å) and the particle mesh Ewald (PME) algorithm (with a 12 Å cutoff) were used to treat van der Waals and electrostatic interactions, respectively. The preparation and production of the MD stages were the same for all peptides and described elsewhere . Finally, MD production runs (duration at least 200 ns each) were conducted in an NPT ensemble at a semi-isotropic pressure and a constant temperature of 310 K with an integration step of 2 fs.…”
Section: Methodsmentioning
confidence: 99%
“…Many reports, including ours, 18 previously identified that four cationic and three hydrophobic residues are required in a peptide for antimicrobial activity and selectivity toward the bacterial membrane. Accordingly, in the initial set of heptameric peptides 1a−e, considering the pivotal role of net charge/hydrophobic ratio, 5 we used four cationic (Arg) and three hydrophobic (Trp) residues (peptides 1a−e, Table 1).…”
Section: Sar-based Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation